Anaesthetic management and incidence of anaesthetic complications in dogs undergoing balloon valvuloplasty for treatment of pulmonic stenosis: a retrospective study - Hjalmarsson, Lydia; Bianchi, Cristina; Hannabuss, Joshua; Stathopoulou, Thaleia (Frontiers in Veterinary Science, 2025)
A retrospective analysis of dogs undergoing balloon valvuloplasty of the pulmonic valve between April 2014 and March 2023 was performed. Anaesthetic records from 44 dogs were included in the analysis. Dogs were grouped according to anaesthetic maintenance agent used, inhalational agent with partial intravenous anaesthesia (PIVA, n = 31) or propofol total intravenous anaesthesia (TIVA, n = 13). Variables including invasive blood pressure, heart rate, incidence of arrhythmias and requirement for interventions in the form of fluid bolus, anticholinergics and vasopressors were compared. Incidence of hypotension was significantly lower in dogs maintained on TIVA (40%) compared to PIVA (79%) (p = 0.008). Total duration of hypotension was shorter in dogs maintained on TIVA (median 40, interquartile range (IQR) 10–62.5 versus median 65, IQR 17.5–110 min) (p = 0.003). Systolic, mean and diastolic blood pressures were significantly higher in patients maintained on TIVA (107 ± 18, 73 ± 10 and 59 ± 8 mmHg respectively) compared to those maintained on PIVA (96 ± 15, 65 ± 9 and 52 ± 8 mmHg respectively, p = 0.039, p = 0.0079, p = 0.0156). No significant differences in incidence of arrhythmias (p = 0.292) and heart rate (88 ± 14 and 88 ± 18 beats minute−1 respectively) (p = 0.953) were seen between the two groups. There was also no significant difference in the number of interventions required to maintain normotension (p = > 0.1).